2017
DOI: 10.1136/jim-2016-000375
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pragmatic Trial of Nasogastric Tube Placement in Patients with Upper Gastrointestinal Tract Bleeding

Abstract: NCT00689754.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…A recent retrospective study and a review both concluded that nasogastric tube (NGT) aspiration does not differentiate upper from lower GI bleeding in patients with melena [73,74]. Moreover, a randomized, single-blind, noninferiority study comparing NGT placement (with aspiration and lavage) to no NGT placement (n = 140 in each arm), failed to show that NGT aspiration could accurately predict the presence of a high risk lesion requiring endoscopic therapy (39 % vs. 38 %, respectively) [75]. In addition, adverse events (pain, nasal bleeding, or failure of NGT placement) occurred in 34 % and there were no observed differences in rebleeding rates or mortality.…”
Section: Nasogastric/orogastric Tube Aspiration and Lavagementioning
confidence: 99%
“…A recent retrospective study and a review both concluded that nasogastric tube (NGT) aspiration does not differentiate upper from lower GI bleeding in patients with melena [73,74]. Moreover, a randomized, single-blind, noninferiority study comparing NGT placement (with aspiration and lavage) to no NGT placement (n = 140 in each arm), failed to show that NGT aspiration could accurately predict the presence of a high risk lesion requiring endoscopic therapy (39 % vs. 38 %, respectively) [75]. In addition, adverse events (pain, nasal bleeding, or failure of NGT placement) occurred in 34 % and there were no observed differences in rebleeding rates or mortality.…”
Section: Nasogastric/orogastric Tube Aspiration and Lavagementioning
confidence: 99%
“…The role of nasogastric lavage has been controversial. In previous studies, a positive lavage was useful in finding the high-risk lesion and it has been associated with the earlier endoscopy, but it was not associated with a change in clinical outcomes [41]. The somatostatin analog, octreotide, is an effective therapy to control GI bleeding, especially when due to angiodysplasia [42].…”
Section: Controversial Medical Therapiesmentioning
confidence: 99%
“…Though a nasogastric tube can be placed to evaluate gastric aspirate for resolution of intragastric bleeding and clearance of clots and particulate, the routine placing of a nasogastric tube for diagnosis or therapeutic effect is not required [18,19].…”
Section: Diagnosis and Managementmentioning
confidence: 99%